3D energy framework strategy by balanced scorecard - R. Roadprasert (2018)
In this paper, the balanced scorecard has been applied to create an ideal national energy framework, which is useful for the specific overall strategic theme, objective, sub-objective and the owner of each objective. The result obtained from a case study shows that it can be used to facilitate the measurement of alternative energy development plan (AEDP 2012-2021) in Thailand and the ideal national energy framework, which can also be applied for the national energy framework creation and presented the overall strategic theme, objective, sub-objective and the owner of each objective under the strategic theme in objective measurement target initiative (OMTI) form. This method can help strategic planners for assigned measurement guideline under each strategic objective to the right owner. Originally, the company in lower chain will receive the policy from the top level organization such as ministry, regulator or country governor. Then, this policy can be used to set own vision, goal and their key performance indicator (KPI), where the problem from information can transfer from low level to top level, which can support the decision maker.